Predicting a ‘Combined Treatment Outcome’ in Chronic Schizophrenia: The Role of Demographics, Symptomatology, Functioning and Subjective Well-being - Naber, D.; Kollack-Walker, S.; Chen, J.; Stauffer, V. L.; Kinon, B. J.; Case, M.; Ascher-Svanum, H.; Kapur, S.; Kane, J. M. (Pharmacopsychiatry, 2013)
The aim of this study was to determine what variables predict a ‘combined treatment outcome’ (COMBOUT) in patients with chronic schizophrenia.This analysis (n=522) was based on a randomized, double-blind, flexible-dose, 12-week study that enrolled chronically-ill patients diagnosed with schizophrenia or a related disorder. COMBOUT was assessed using the PANSS for symptoms, CGI-S for overall clinical status, MADRS for depressive symptoms, QLS for functioning/QOL, and SWN-K for subjective well-being. Possible predictors included demographics as well as baseline scores (Model I), and early change (week 2) scores (Model II).Model I: significantly better outcome (higher COMBOUT score) was observed in patients with lower MADRS (T= − 6.36; p<0.001) or higher QLS (T=5.05; p<0.001) scores at baseline. Model II: significantly better COMBOUT was observed in patients with early improvement of QLS (T=4.93; p<0.001), SWN-K (T=3.88; p<0.001), PANSS (T= − 2.32; p=0.021) and CGI-S scores (T= − 2.22; p=0.027). Changes in EPS were not predictors of COMBOUT in the models tested.COMBOUT at endpoint was predicted by lower depressive symptom score and higher QOL at baseline and by early improvement in psychopathology, quality of life and subjective well-being.
Keywords: schizophrenia; risperidone; olanzapine; antipsychotics; prediction